Avaliação histomorfométrica dos efeitos da movimentação dentária induzida sobre molares de ratos submetidos à luxação extrusiva - Verri, Ana Caroline Gonçales [UNESP] (2015)
Introduction: Traumatism in the supporting periodontium is dangerous in the Orthodontic area since orthodontic treatment depends on its integrity. Objective: The aim of this study was to evaluate effects of induced dental movement in teeth that were submitted to extrusive luxation evaluating: inflammatory infiltrated, giant cells and root resorption. Materials and Methods: Sixty Wistar male rats were divided in 6 groups (n=10): Group 1 (Control); Group 2 (Traumatized Control of 5 days); Group 3 (Traumatized Control of 7 days); Group 4 (Movement Control of 7 days); Group 5 (Traumatized of 5 days and Movement of 7 days); Group 6 (Traumatized of 7 days and Movement of 7 days). The upper right first molar was microscopically examined to determine the histopathological events of induced dental movement and histomorphometrical analysis of depth of root resorption. Results: In the experimental groups (5 and 6) the most expressive microscopic alterations were dental root resorption of cervical and medium third of mesial periodontium of distal-buccal root; intense acute inflammatory infiltrated; giant cells near from root resorption areas, showing active root resorption; lower volume of inter root septum and no pulpal necrosis. Analysis of depth of root resorption showed low occurrence that did not exceed 50%. In the group 6 the resorption was deeper compared with other groups and presented statistically significant difference in relation to its controls (P<0.05). Conclusion: Association between induced dental movement and extrusive luxation generates higher levels of histopathological events and resorption areas in the dental root significantly higher 7 days after induced trauma (G6)